Biofertilizer potential of digestates from small-scale biogas plants in the Cuban context - Odales, Leyanet; López, Edelbis; López, Lisbet Mailin; Jiménez, Janet; Barrera, Ernesto Luis (Revista de Ciencias Agrícolas, 2020)
The residual sludge from anaerobic digestion known as digestate has been used as a valuable biofertilizer, but the effect of the substrate, the configuration of the reactor and the operating parameter changes the quality and amounts of nutrients in it. Therefore, it is necessary to know its potential characteristic of fertilizer to apply it correctly in crops of national interest. The aim of this work was to characterize the digestate generated from three biodigester technologies (fixed dome, floating drum and tubular) and three substrates: swine manure, cow manure, and co-digestion of swine and cow manure obtained in the province of Sancti Spíritus, Cuba, in terms of nutrient and matter content. For this purpose, stratified statistical sampling was carried out to ensure representative samples and descriptive statistical techniques were used to process the analyses. The digestate was divided into liquid and solid fractions according to the dry matter content (15%). The content of organic matter and ash represented around 50% for both fractions, which enhances its value as a soil conditioner. The nutrient content of both fractions showed good fertilizing properties, having a nutrient ratio (NH4+:PO43-:K+:SO42-:Mg2+:Ca2+) in the liquid (0.002:0.80:0.10:1.00:0.89:0.93) and solid (0.0003:0.96:0.002:1.00:0.52:0.50) fractions, that would contribute to the return nutrients to the soil. The quality of the liquid fraction as irrigation water was assessed as good, according to the relationship between the concentration of the nutrients (Ca, Mg, Na and K) and hardness. Further research is needed on the appropriate dosage for the different crops, and its contribution to sustainable agriculture in the Cuban context.